IMMUNO AND MOLECULAR EPIDEMIOLOGY OF PLASMODIUM VIVAX BLOOD STAGE ANTIGENS UNDER LOW TRANSMISSION AND UNSTABLE MALARIA CONDITIONS IN SRI LANKA - Wickramarachchi, W. T. A. (Faculty of Science, University of Colombo, 2005)
Data generated through Immuno and molecular-epidemiology studies are imperative in vaccine development studies. In this context, exploration of the nature of naturally acquired immune responses, in vivo correlates of protection and the genetic polymorphism among Plasmodium parasite populations, are of significant relevance for anti-malarial vaccine development. ...